Formation Of Logical Thinking Skills Among Students In Preschool Educational Organizations - Dekhkonova Iroda Golipovba; Rakhima Pozilovna Mannopova; Karimova Mashkhura daughter of Rustamjon (Genius Journals, 2023)
At present, the issue of preparing a child for schooling with account for his age, psychophysiological and individual characteristics is high on the agenda. The importance of the problem lies in the search for new methods and technologies aimed not only at the development of certain skills, but rather at the overall, harmonious and all-round development of the child, which allows him not only to preserve but also to increase his resource potential. The article illustrates the method of pictograms, which allows forming verbally-logical and abstract-logical thinking in children (at the initial level at this point) already at the stage of preschool childhood.
Keywords: preschool education; pictogram method; pictographic record